A3 Studying and managing the behavioural phenotypes of Huntington's disease. Issue 10 (7th September 2012) - Craufurd, D
Abstract : Honorary Consultant in Neuropsychiatric Genetics. David graduated in Medicine from London University (St. Bartholomew's) in 1976 and moved to Manchester to study Psychiatry in 1979. After completing his training in general psychiatry, he arranged a temporary secondment to Clinical Genetics in 1986 to pursue an interest in the genetic aspects of psychiatric disorders, and ended up "going native". He is now a senior lecturer and honorary consultant in neuropsychiatric genetics. His research interests are concerned mainly with the neuropsychiatric aspects of Huntington's disease (HD), and with the psychological and social impact of predictive DNA testing for late-onset genetic disorders. He set up the UK's first multidisciplinary management clinic for HD, currently the largest contributing site to the European HD Network (EHDN) case registry, and is actively involved in a number of European and worldwide research projects and clinical trials. He is a member of the Scientific Review Committee of the EHDN, leads the EHDN Behavioural Phenotype Working Group and is a former Secretary-General of the World Federation of Neurology Research Group on HD. He is co-Director of the MSc programme and teaches on the Clinical Genetics and Advanced Genetic Counselling modules. Behavioural symptoms have been recognised as a key component of the clinical phenotype of HD ever since the first description by Huntington in 1872, but remain a relatively under-researched aspect of the condition. Depression has received more attention than other psychiatric symptoms, but factor analysis of several large datasets has revealed that apathy and irritability are more common, and arguably cause more distress and disability. Longitudinal analysis of behavioural symptoms has confirmed that these three symptom clusters follow different trajectories over time, suggesting that each has a different neurobiological basis, and recent imaging studies lend some support to this hypothesis. It has long been recognised that many affected individuals display characteristic behavioural changes for some years before the onset of motor symptoms, and there has been considerable recent interest in the possibility of using these early manifestations as end points for clinical trials of disease-modifying interventions in known gene carriers prior to diagnosis. However, it has proved difficult to detect substantial changes in well-conducted longitudinal studies of pre-manifest subjects such as PREDICT and TRACK-HD. One reason may be the emergence of impaired insight (or denial) as the behavioural symptoms begin to occur, a phenomenon which has been noted by clinicians for many years; another is likely to be the use of concomitant medication for symptomatic treatment. Mood disturbances, anxiety, irritability and perseveration all respond to treatment with serotonin reuptake inhibitors, but apathy may be exacerbated by the use of neuroleptic medication for symptomatic treatment of involuntary movements or aggressive behaviours.